Digital local supply on the rise? Determinants of multi- and cross-channel shopping behaviour in grocery retailing - Wieland, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Multi- and cross-channel integration of German grocery retailing appears in terms of online-based delivery services and click-and-collect offers by established supermarkets. However, these trends raise the question whether digital services may complement established distribution channels, especially with respect to local supply. This paper describes the investigation of the maindeterminants of spatial shopping behaviour in the food retail sector. In particular, it was examined whether grocery stores can benefit from the click-and-collect option and which factors determine the choice ofshopping location if both stationary and online providers are available. Individual store choices and the related expenditures at grocery retailers are investigated using a micro-econometric store choice model (hurdle model) based on a representative customer survey in two German regions (South Lower Saxony, Region Middle Upper Rhine). Pure grocery online retailing is found to have little relevance, whilst supermarkets gain little profit from offering the click-and-collect option. The likelihood of buying groceries online can be explained by psychographic characteristics of the consumers. In a situation where consumers may choose between offline and online retailers, channel-specific transaction costs (driving time, shipping charges) can be identified as important determinants of store choice.